GE_GERICHTE C/23100/2014 vom 29. Juni 2018 - GE Cour de justice (2018)
DROIT DE GARDE ; GARDE ALTERNÉE ; VISITE ; ENFANT ; OBLIGATION D'ENTRETIEN ; CONTRIBUTION DE PRISE EN CHARGE | CC.133.al1; CC.273.al1; CC.276; CC.285.al1; CC.125.al1